Conference on Lasers and Electro-Optics 2021
DOI: 10.1364/cleo_at.2021.am4o.5
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement Distribution and Routing in a Multi-node Quantum Network Testbed

Abstract: We report a field test of distribution and reconfigurable routing of multichannel entangled photons in a quantum network testbed. Nonlocal dispersion cancellation has been leveraged to maintain high-quality entanglement in the quantum network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…In our recent conference paper [16] we have shown that by using this concept we can generate bright entangled photons enabling the distribution of entanglement even over terrestrial free-space optical links in the presence of strong turbulence. So far either fiber-optics links [33] or satellite-to-ground links [34] have been used to distribute entanglement. Moreover, the PPLN waveguides have already been used in fiber-optics communications to perform the phase-conjugation of the whole WDM comb [20] to deal with fiber nonlinearities.…”
Section: Generation Of Entangled States Employing Telecom C-band Devicesmentioning
confidence: 99%
“…In our recent conference paper [16] we have shown that by using this concept we can generate bright entangled photons enabling the distribution of entanglement even over terrestrial free-space optical links in the presence of strong turbulence. So far either fiber-optics links [33] or satellite-to-ground links [34] have been used to distribute entanglement. Moreover, the PPLN waveguides have already been used in fiber-optics communications to perform the phase-conjugation of the whole WDM comb [20] to deal with fiber nonlinearities.…”
Section: Generation Of Entangled States Employing Telecom C-band Devicesmentioning
confidence: 99%